A Governance and Risk Inventory for a Changing Arctic: Background Paper for the Arctic Security Roundtable at the Munich Security Conference 2020 - Rowe, Elana Tovah Wilson; Sverdrup, Ulf; Friis, Karsten; Hønneland, Geir; Sfraga, Michael (Munich Security Conference, 2020)
Input report 2020 by the Norwegian Institute of International Affairs / Wilson Center Many government officials, military leaders, and political observers have proclaimed the rise of a new, post-Cold War global great power competition between the United States, Russia, and China with myriad implications. Using this new reality as the backdrop for the Arctic Security Roundtable at the Munich Security Conference 2020, roundtable participants are asked to explore, discuss, and debate this issue in the context of, and implications for the new globalized Arctic. This paper – a primer of Arctic trends, risks, and institutions – provides a useful starting point for the discussion. Discussing Arctic security in high-level forums is important. One might ask why we should take the time to discuss the Arctic if we are not fighting a war there. The answer is this: there is a new ocean opening up due to global climate change. There is a promising track record of governance cooperation in the region that serves as a basis for pursuing sustainable management of and peace in this new ocean. The point of dialogue – with an emphasis on cooperation, joint governance and outlining risks and potential tipping points – is to make sure that we do not add the Arctic to the already far-too-long list of global hot spots. The Arctic Security Roundtable at the Munich Security Conference 2020 provides one such confidential forum for proactive and constructive debate on Arctic security issues.